Brainstorming Business Model Canvas Pada Formulasi Strategi Optimalisasi Sedimentasi Tailing Tambang Emas Pada Pertambangan Emas Skala Kecil di Koperasi Produsen Tombang Tujuah Loge - Yusriwarti, Yusriwarti; Alpiyandri, Alpiyandri; Zulfhi Surya, Roberta (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Alluvial gold mining tailings in Logas consist of sand and mud, which are dominated by silica minerals and feldspar; the fine sand size fraction and the picking fraction are dominated by silica minerals, metals, and other high-hardness minerals. Tailings pose a new problem, namely sedimentation, which results in the silting of rivers, which causes flooding and damages community plantations. Tailings still have economic value, which can provide a source of income for the Tombang Tujuah Loge Producers Cooperative. This study formulates the idea of